Elasticidade de oferta de ovos e demanda de insumos avícolas no estado do Amazonas - Pinto Ribeiro, Ricardo; Aad Neto, Alexandre; Martins Rezende, Alberto; da Paz Puga Rebello, Armando; Fagundes de Sousa, Antônio; Brandt, Sérgio Alberto (Revista Ceres, 2025)
It is believed that a better understanding of the relatio- ships among production response, price incentives and farm credit would be of real value in developing public policies in these areas and at the same time guarantee egg producers an income in the state of Amazonas and a supply of food for the growing population of Manaus. An empirical analysis of supply response could represent a significant contribution to the development of these policies. The objectives of this supply function study could be summa- rized as follows: (a) to improve understanding of the mechanism of eggs production response, (b) improve predictions of eggs production changes, (c) improve the effectiveness of policies affecting eggs supply, and (d) improve the understanding of the impact of programs of importation, exportation, taxation, and incentiveson eggs production and income.